CFD Simulations of Vapour-Liquid Separator in LNG Process - Mahadika Priyambodo, Muhammad Dary; Sun, Biao; Bhatelia, Tejas; Utikar, Ranjeet; Pareek, Vishnu; Byfield, Geoffrey (2019)
In natural gas processing, vapour-liquid separation (VLS) is one of the commonly used unit operations. In this paper, a series of Computational Fluid Dynamics (CFD) simulations were conducted on an industrial scale VLS. Initially, simulations were carried out to evaluate the performance of inlet diverter by studying the effect of inlet Reynolds number on the crosssectional variance of velocity. It was found that the flow was highly symmetrical and evenly distributed with a variance nearly zero at a very low Reynolds number (Re = 1000), but as the inlet Reynolds number increased, the variance increased to 0.03 and the flow was highly dominated towards the wall. To simulate the Knitmesh, porous media was used with inertial and viscous resistance calculated and validated using previously published experimental data (Rahimi and Abbaspour 2008). When a full scale VLS was simulated, it was found that at industrially relevant condition the effect of inlet diverter was significant on the Knitted mesh mist eliminator performance and approx. 88% of it was subject to velocities above the prescribed terminal velocity and would lead to poor vapor liquid separation. Without any hardware change to mitigate this underperformance, it would be required to drop the capacity of the VLS by at least 5 times. On the other hand, if two layers of mist pads with 75% size of full mesh pad was used, 26% recovery in performance can be achieved. The model proposed in this work provides the basis for future development of parametric study on various configurations of mesh pad that can ultimately improve the capacity and performance of the VLS.